Investigating a relationship between learner control and self-efficacy in an online learning environment - Widchaporn Taipjutorus; Sally Hansen; Mark Brown (Flexible Learning Association of New Zealand, 2012)
In both traditional face-to-face and online learning contexts, self-efficacy has been shown to be a key contributor to learner success. Once established, self-efficacy can be generalised to other learning situations, with the strongest effect occurring with learning activities that are closest to those in which self-efficacy has been improved. Self-efficacy is not only a good predictor of learners' academic outcomes, but efficacious learners also tend to persist, cope, and adapt well, even when they have no prior experience. Learners who have low confidence in their ability to study can become frustrated, overwhelmed, and demotivated-they are more likely to achieve low grade point averages, and in some cases drop out. When people become online learners, especially for the first time, they may feel less confident, despite being familiar with day-to-day computer and technology usage. They may still lack essential learning and technology skills for tertiary education and online learning. To support these learners, online courses should be designed to foster learners' efficacy. Research findings have shown that embedded learner control in online modules can enhance learning, improve attitudes, and increase self-efficacy. However, little research has been done to examine self-efficacy of online learners with different levels of learner control in a real online class setting. Therefore, this paper describes current research that focuses on this gap in research, and uses a quantitative research design to investigate the relationship between learner control and learner self-efficacy. Online learning self-efficacy scales and a set of questionnaires were developed and validated. In a pilot study, 31 postgraduate online learners were asked to assess their own self-efficacy and experience with different levels of learner control. Preliminary results show a positive relationship between learner control and online learning self-efficacy.